Review of strategies to recruit smokers for smoking cessation: a population impact perspective Revisão sobre estratégias de captação de fumantes: o olhar do impacto populacional - André Salem Szklo (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2008)
This paper reviews published articles describing several instruments used currently to "capture" the attention of smokers for quit-smoking interventions and emphasizes the distinction between the strategies used to reach eligible individuals and those used to recruit them for the proposed smoking cessation intervention. The search for articles was conducted using MEDLINE, PsychARTICLE, and LILACS. Key words for the search included recruitment, enrollment, reach, smoking cessation, quitline, and helpline mentioned in the abstracts and titles of the articles. Articles published in English, Portuguese, and Spanish through November 2006 that emphasized capture instruments related to different populations and specific interventions were included in this review. Twenty-nine studies met the inclusion criteria. Studies that used active and mixed strategies reached, on average, a smaller and less diverse possible number of eligible individuals and had greater participation proportions than those that used reactive strategies. Future studies are needed to evaluate the effectiveness of new associations between current interventions and reactive capture strategies, in view of the potential for increasing the population impact related to reactive capture. Este artigo revisou artigos publicados sobre diversos instrumentos empregados atualmente para "capturar" a atenção dos fumantes, ressaltando a diferença existente entre alcance e recrutamento da população elegível para intervenção proposta. Realizou-se uma busca nas bases MEDLINE, PsychARTICLE, e LILACS. Os descritores de busca combinaram as palavras recruitment, enrollment, reach, smoking cessation, quitline, e helpline presentes nos resumos/títulos dos artigos. Artigos publicados em inglês, português e espanhol até novembro de 2006, que deram importância a instrumentos de captação empregados, associando os mesmos a populações diferentes e a intervenções específicas foram incluídos na revisão. Vinte e nove estudos atenderam os critérios de inclusão. Estudos que utilizaram estratégias ativas ou mistas alcançaram, em média, um menor e menos diversificado número possível de indivíduos elegíveis e obtiveram maior proporção de participação do que aqueles que utilizaram estratégias reativas. Estudos futuros são necessários para se avaliar a efetividade de novas associações entre as intervenções existentes e estratégias reativas de captação, dada a potencialidade de aumento do impacto populacional relacionada à captação reativa.